'Miracle baby': an outcome of multidisciplinary approach to neurotrauma in pregnancy. (17th July 2012) - Neville, Grace; Kaliaperumal, Chandrasekaran; Kaar, George
Abstract : Traumatic brain injury (TBI) warranting neurosurgical intervention in the pregnant population is a rarity. We describe a case of a 27-year-old woman who at 13 weeks of gestation presented with multiple traumas having been involved in a near fatal road traffic accident. Glasgow Coma Scale was 6/15. CT brain showed extensive haemorrhagic contusions, diffuse brain swelling and multiple skull and facial fractures. Decompressive craniectomy was performed to control her intracranial pressure during her management in the intensive care. A viable intrauterine pregnancy was confirmed and progressed as maternal stabilisation and rehabilitation continued. At 35+3 weeks a 2770 g male child was delivered via emergency caesarean section after spontaneous onset of labour. The child had no detectable abnormalities and is clinically well. Eight months post-TBI the patient continues to make gradual improvements but is left with severe cognitive impairment and currently undergoing rehabilitation. A multidisciplinary approach was adopted in the management of this patient.